Characterization of microbiota and secretory Ig-A in the domestic duck (Anas platyrhynchos) small and large intestine - R. SUSANTI; NUR RAHAYU UTAMI; ARI YUNIASTUTI (Society for Indonesian Biodiversity, 2023)
Abstract. Susanti R, Utami NR, Yuniastuti A. 2023. Characterization of microbiota and secretory Ig-A in the domestic duck (Anas platyrhynchos)small and large intestine. Biodiversitas 24: 2458-2466. The Microbiome composition could affect the duck's intestines' microenvironment, which may shape the microstructure's anatomy, metabolism, and immune system. Therefore, this study aims to characterize the intestinal microbiome's abundance, diversity, and IgA distribution in ducks' intestines. This study took 15 healthy domestic ducks (Anas platyrhynchosLinnaeus, 1758) from an intensive duck farm in Central Java, Indonesia. Five grams of each small and large intestine content were collected aseptically for metagenomic analysis. Then, the intestine organs were taken for immunohistochemistry preparations to depict the IgA distribution. The results showed that the small intestine has a greater bacterial abundance community, with 18 phyla, while only 13 are found in the large intestine. Interestingly, three phyla: Firmicutes, Actinobacteria, and Bacteroidetes, were found dominantly in both organs. However, the comparison of Firmicutes and Bacteroidetes ratio was higher in the small intestine (2357.76) than large intestine (10.64). The IgA distribution in the small and large intestines showed intermediate staining intensity (score: 2.07-2.20) and a final Allred score of 5.0 (positive). Even though dysbiosis microbiome was present in intestines with dominant species Streptococcus and Enterococcus, it seems no significant IgA over secretion. Understanding duck's gut immune response is important because it is highly tolerant to the pathogens that make them play an important role as an environmental reservoir for pathogenic viruses and bacteria and may potentially comprehend future infectious disease outbreaks.